What the eyes don`t see: an objective assessment of players` contribution to team success in men`s rugby league - Cameron, S.; Radwan, I.; Mara, J. (Research Quarterly for Exercise and Sport, 2025)
Purpose This study addresses the lack of objective player-based metrics in men`s rugby league by introducing a comprehensive set of novel performance metrics designed to quantify a player`s overall contribution to team success.